Geo-info to-go - Kamal Baharin, S. S. (2007)
The mission of the Dutch grant program ‘Space for Geo-information’ (Ruimte voor Geoinformatie, www.rgi.nl) is described as “the enhancement and innovation of the geoinformation infrastructure and the geo-knowledge community in the Netherlands”.One of the projects (RGI-149)currently undertaken within this program is called ‘Geo-info-togo’.